Influences of age, tongue region, and chorda tympani nerve sectioning on signal detection measures of lingual taste sensitivity - Doty, Richard L.; Heidt, Julie M.; MacGillivray, Michael R.; Dsouza, Merle; Tracey, Elisabeth H.; Mirza, Natasha; Bigelow, Douglas (Physiology & behavior, 2016)
Although the ability to taste is critical for ingestion, nutrition, and quality of life, a clear understanding of the influences of age, sex, and chorda tympani (CT) resection on taste function in different regions of the anterior tongue is generally lacking. In this study we employed criterion-free signal detection analysis to assess electric and chemical taste function on multiple tongue regions in normal individuals varying in age and sex and in patients with unilateral CT resections. The subjects were 33 healthy volunteers, ranging from 18 to 87years of age, and 9 persons, 27 to 77years of age, with unilateral CT lesions. The influences of age, sex, tongue region, and chorda tympani resections on signal detection sensitivity (d′) and response bias (β) measures was assessed in 16 tongue regions to weak electric currents and solutions of sucrose, sodium chloride, and caffeine. Significant age-related decrements in d′ were found for sucrose (p=0.012), sodium chloride (p=0.002), caffeine (p=0.006), and electric current (EC) (p=0.0001). Significant posterior to anterior, and medial to lateral, gradients of increasing performance were present for most stimuli. β was larger on the anterior than the posterior tongue for the electrical stimulus in the youngest subjects, whereas the opposite was true for sucrose in the oldest subjects. No sex differences were apparent. d′ was depressed ipsilateral to the CT lesion side to varying degrees in all tongue regions, with the weakest influences occurring on the medial and anterior tongue. CT did not meaningfully influence β. This study is the first to employ signal detection analysis to assess the regional sensitivity of the tongue to chemical and electrical stimuli. It clearly demonstrates that tongue regions differ from one another in terms of their age-related sensitivity and their susceptibility to CT lesions. •Criterion-free signal detection analysis applied to regional taste testing.•Age differentially influences taste in different tongue regions.•Chorda tympani damage differentially alters taste function in different tongue regions.•Tongue tip less affected by chorda tympani lesions than other tongue regions.•Posterior to anterior, and medial to lateral, gradients of taste sensitivity noted.